Robobees Way to future or avoiding nature - Kalla, Pushpa; Saha, Samrat; Nath, Riju (Indian Farming, 2024)
Pollination is the basic pillar of our food production, and in this respect, different hymenopteran bees play a crucial role. However, with technological advancements, our world is moving towards a situation that is inviting an enforced ‘bee decline’ or more broadly ‘pollinator crisis’. There are many reasons responsible for this phenomenon, like heavy use of chemicals, habitat loss, infestation of parasites and diseases, urbanization, etc. To tackle this situation, roboticists from different corners of the world are coming with a solution, i.e., robobees in place of natural bees. These robobees are micro robots imitating the buzz pollination of bees. However, robotic crop pollination is technologically and economically a non-viable solution to naturally occurring bee pollination. There are arguments regarding its efficiency as compared to natural bees, its ecological and economical constraints, its impact on biodiversity as well as on ecosystem services, etc. In simple words, these robobees are not the answer to ‘bee decline’.